Polyethylene glycol-coated graphene oxide attenuates antigen-specific IgE production and enhanced antigen-induced T-cell reactivity in ovalbumin-sensitized BALB/c mice - Wu HY (Dove Medical Press, 2014)
Hsin-Ying Wu,1,* Kun-Ju Lin,2,* Ping-Yen Wang,1 Chi-Wen Lin,3 Hong-Wei Yang,3 Chen-Chi M Ma,3 Yu-Jen Lu,4 Tong-Rong Jan1 1Department and Graduate Institute of Veterinary Medicine, School of Veterinary Medicine, National Taiwan University, Taipei, Taiwan; 2Animal Molecular Imaging Center and Department of Nuclear Medicine, Chang Gung Memorial Hospital, Tao-Yuan, Taiwan; 3Department of Chemical Engineering, National Tsing Hua University, Hsin-Chu, Taiwan; 4Department of Neurosurgery, Chang Gung Memorial Hospital, Tao-Yuan, Taiwan *These authors contributed equally to this work Background: Graphene oxide (GO) is a promising nanomaterial for potential application in the versatile field of biomedicine. Graphene-based nanomaterials have been reported to modulate the functionality of immune cells in culture and to induce pulmonary inflammation in mice. Evidence pertaining to the interaction between graphene-based nanomaterials and the immune system in vivo remains scarce. The present study investigated the effect of polyethylene glycol-coated GO (PEG-GO) on antigen-specific immunity in vivo. Methods: BALB/c mice were intravenously administered with a single dose of PEG-GO (0.5 or 1 mg/kg) 1 hour before ovalbumin (OVA) sensitization, and antigen-specific antibody production and splenocyte reactivity were measured 7 days later. Results: Exposure to PEG-GO significantly attenuated the serum level of OVA-specific immunoglobulin E. The production of interferon-γ and interleukin-4 by splenocytes restimulated with OVA in culture was enhanced by treatment with PEG-GO. In addition, PEG-GO augmented the metabolic activity of splenocytes restimulated with OVA but not with the T-cell mitogen concanavalin A. Conclusion: Collectively, these results demonstrate that systemic exposure to PEG-GO modulates several aspects of antigen-specific immune responses, including the serum production of immunoglobulin E and T-cell functionality. Keywords: graphene oxide, T-cell, antigen-specific, immune, ovalbumin